THE CULTURAL TYPES AND IDENTITY OF SUNAN KALIJAGA TEMBANG DOLANAN LIR-ILIR ANALYSIS OF DENOTATION AND CONOTATION - Yehezkiel Antonius Wijayanto; Rahmawati Zulfiningrum (Jurnal Ilmu Komunikasi Acta Diurna, 2023)
Most of the surviving cultural arts are representations of the real life of the community, the higher the cultural values and messages offered, the longer they last across generations. This study aims to determine the moral values contained in Tembang Lir-ilir as a means of preaching Sunan Kalijaga during the spread of Islam in Java. This study uses an ethnographic approach in data collection, as well as a discussion of the Theory of Cultural Types, Cultural Identity and General Semantics. The results of the study show that Tembang Dolanan Lir-ilir has survived to the present day as follows: 1) Efforts to preserve Tembang Dolanan Lir-ilir by using educational facilities to sing this song either in daily lessons or at certain events at school; 2) Efforts to utilize regional arts and religious facilities; 3) Efforts to develop using popular arrangements among the public, dissemination of songs via the digital channel Youtube to spread songs. The people of Demak Regency have a passion for supporting the existence of Tembang Dolanan Lir-ilir. There needs to be outreach to the public in understanding the philosophical values of Javanese culture contained in the lyrics of Tembang Dolanan Lir-ilir.